جذور - عسيلة, بيان; المصري, ملاك; أبو عرقوب, تيمه; العواودة, دنيا (جامعة بوليتكنك فلسطين - ادارة اعمال, 2024)
بروشور يتضمن ثالثة معالم داخل باحات المسجد األقصى، وكل معلم له ٌ فيلم ٌ وثائقي خاص به يربط بين البرشور ًة تساعد في معرفة موقع وكل فيلم "QR "ينقلنا إلى منصة اليوتيوب للمشاهدة، ويتضمن بنهاية البرشور خريط ًة تفاعلي كل منهما، باإلضافة إلى معلومات وصور تعريفية وفي نهاية المشروع، سيتم عرضه خالل يوم المناقشة في جامعة بوليتكنك فلسطين -كلية العلوم اإلدارية -مبنى أبو رمان، وسيتم توزيعه على مواقع التواصل االجتماعي الخاصة بالجامعة. A brochure featuring three landmarks within the courtyards of the Al-Aqsa Mosque, with each landmark having its own documentary film linked in the brochure by a barcode that directs to the YouTube video for viewing, At the end of the brochure there is an interactive map that helps locate each one of the landmarks , along with informative text and images. At the end the project will be presented during the discussion day at Palestine Polytechnic University - Faculty of Administrative Sciences - Abu Raman Building, and will be distribute on the university's social media platforms.
no of pages 64, جرافيكس 2024
Keywords: الاعلانات التعريفية